Unfiltered : sediment alterations in response to untreated wastewater emissions from a marine outfall off Ísafjörður, Iceland - Thompson, Jake Maruli, 1993- (2020)
An ecosystem’s ability to sustainably handle wastewater inputs relies on the relationship between the receiving environments natural processes, flow rate, and amount and composition of the wastewater. A benthic survey was conducted to investigate the impacts of a singular wastewater outfall (point source pollution) in Ísafjörður, Iceland, which lacks primary treatment. Direct observation conducted by scuba dives close to the wastewater outfall allowed for the preliminary assessment of the area documented through transect monitoring using underwater photography and video capture. A series of sediment core samples from the benthic zone were subsequently taken and analysed for Total Oxygen Uptake (TOU), Oxidation Reduction Potential (ORP) and pH. The sediment samples were collected from around the wastewater outfalls, in addition to a comparable reference a non-polluted reference site in Álftafjörður. To evaluate oxygen consumption rates and thus the pressure from pollution, measurements were undertaken periodically within each sample. The results indicated that oxygen consumption rates were highest in sediment 7m from the outfall in Pollurinn. Comparing the two sites, a statistical significance was measured between the ORP measurements (p=0,009), indicating increased benthic mineralization possibly due to pollutants settlement from the outfall. Observable differences in TOU and pH also supporting increased benthic mineralization around the outfall, but do not show statistical significance. Rural communities lacking ready access to equipment for wastewater analysis can adapt methodologies used in this report to better understand the affects and impact of wastewater pollution on the sea floor and the immediate environment. Although this surface water monitoring around wastewater outfalls is completed in Pollurinn, the findings suggest approaches should include periodic monitoring of the seafloor. There is also significant room to improve wastewater management including the immediate installation of drainage nets ...